Sunitinib‐Induced Cardiotoxicity Is Mediated by Off‐Target Inhibition of AMP‐Activated Protein Kinase - Kerkela, Risto (Blackwell Publishing Inc, 2009)
Tyrosine kinase inhibitors (TKIs) are transforming the treatment of patients with malignancies. One such agent, sunitinib (Sutent, Pfizer, New York, NY, USA), has demonstrated activity against a variety of solid tumors. Sunitinib is “multitargeted,” inhibiting growth factor receptors that regulate both tumor angiogenesis and tumor cell survival. However, cardiac dysfunction has been associated with its use. Identification of the target of sunitinib‐associated cardiac dysfunction could guide future drug design to reduce toxicity while preserving anticancer activity. Herein we identify severe mitochondrial structural abnormalities in the heart of a patient with sunitinib‐induced heart failure. In cultured cardiomyocytes, sunitinib induces loss of mitochondrial membrane potential and energy rundown. Despite the latter, 5′ adenosine monophosphate‐activated protein kinase (AMPK) activity, which should be increased in the setting of energy compromise, is reduced in hearts of sunitinib‐treated mice and cardiomyocytes in culture, and this is due to direct inhibition of AMPK by sunitinib. Critically, we find that adenovirus‐mediated gene transfer of an activated mutant of AMPK reduces sunitinib‐induced cell death. Our findings suggest AMPK inhibition plays a central role in sunitinib cardiomyocyte toxicity, highlighting the potential of off‐target effects of TKIs contributing to cardiotoxicity. While multitargeting can enhance tumor cell killing, this must be balanced against the potential increased risk of cardiac dysfunction.